Benefits of Using The Pause after Death in Emergency Departments: A Delphi Study. Issue 9 (September 2019) - Cunningham, Tim; Ducar, Dallas M.
Abstract : Objective: The Pause is a short-term, microbreak created by an emergency nurse in 2009. It provides care team members a few seconds of silence to honor a patient who has died while also honoring the efforts of the team. It is used now on four continents as a standard of care. We investigated how it is being used and why. Methods: We used a modified Delphi methodology with purposive sampling and a descriptive approach. During the three-round Delphi, we created a data display using open, then axial coding to develop a thematic analysis. Member checking and reflexivity exercises were used to build reliability and trustworthiness of findings. Results: We analyzed 21 transcripts. The Pause is reported to be an ongoing practice in at least 23 health systems globally. Key themes such as Benefits, Self-Care, and Support of other Patients were most pertinent in our analysis. Conclusion: The Pause is a low-risk, grassroots intervention that can be led by any member of a care team in emergency settings. It offers self-care for the individual and team. It helps emergency providers feel grounded after a death before going to treat another patient. According to our sample, The Pause helps reduce caregiver stress, which may decrease the risk for burnout. Although further research is recommended, we assert that The Pause be used as a standard of care in emergency departments across the United States. Abstract : The Pause is a contemplative practice used in at least 23 health systems internationally. The authors' research suggests that it is a form of self-care for the provider and the team caring for a patient who has died unexpectedly. This is a feasible practice, which may reduce caregiver stress and should be considered as a standard of practice in emergency settings.